2016
DOI: 10.1097/coh.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and immune activation

Abstract: Purpose of review To explore new data from recent studies addressing the role of co-infections in immune activation in HIV-1 infected patients, with a focus on Immune Reconstitution Inflammatory Syndrome (IRIS), an aberrant inflammatory response occurring shortly after antiretroviral therapy (ART) initiation. Recent findings Chronic HIV infection is associated with a number of co-infections that contribute to immune activation in various settings including early after ART initiation in the most noticeable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 85 publications
1
53
2
4
Order By: Relevance
“…Treating a TB and HIV coinfection is clinically challenging; drug interference and toxicity prevents the respective treatments from being combined, leading clinicians to favor one treatment over the other (Djimeu and Heard, 2019). It has been shown that TB-associated immune reconstitution inflammatory syndrome can develop when ART is initiated (Worodria et al, 2011;Abay et al, 2015;Haridas et al, 2015;Boulougoura and Sereti, 2016). Importantly, ART-controlled HIV infection appears to interfere with TB infection (Worodria et al, 2018;Holmberg et al, 2019).…”
Section: Mycobacterium Tuberculosis In Adipose Tissuementioning
confidence: 99%
“…Treating a TB and HIV coinfection is clinically challenging; drug interference and toxicity prevents the respective treatments from being combined, leading clinicians to favor one treatment over the other (Djimeu and Heard, 2019). It has been shown that TB-associated immune reconstitution inflammatory syndrome can develop when ART is initiated (Worodria et al, 2011;Abay et al, 2015;Haridas et al, 2015;Boulougoura and Sereti, 2016). Importantly, ART-controlled HIV infection appears to interfere with TB infection (Worodria et al, 2018;Holmberg et al, 2019).…”
Section: Mycobacterium Tuberculosis In Adipose Tissuementioning
confidence: 99%
“…A rapid increase in the number of CD4 + T cells present likely plays a critical role in the development of IRIS, as evidence suggests that a high baseline CD4 + T cell count is protective against developing IRIS, and conversely lower CD4 + T cell counts are predictive of IRIS development [139,140]. Thus, IRIS occurs while adaptive immunity is being restored following immunosuppression [141,142]. …”
Section: Unique Immunoregulatory Circumstancesmentioning
confidence: 99%
“…The introduction of combination ART in 1995-1996 substantially reduced the incidence of AIDSrelated, CMV-associated end-organ diseases [15]. CMV still contributes to morbidity and mortality in patients who initiate ART with low CD4 + T-cell counts, occasionally as a result of immune reconstitution inflammatory syndrome [16]. Many adults are initially infected with CMV during childhood or early adulthood, although the incidence continues to rise throughout adulthood, by approximately 1% annually [17].…”
Section: Epidemiology and Pathogenesis Of CMVmentioning
confidence: 99%